2018
DOI: 10.1371/journal.pone.0199716
|View full text |Cite
|
Sign up to set email alerts
|

QTL analysis reveals quantitative resistant loci for Phytophthora infestans and Tecia solanivora in tetraploid potato (Solanum tuberosum L.)

Abstract: Late blight and Guatemalan potato tuber moth caused by Phytophthora infestans and Tecia solanivora, respectively, are major phytosanitary problems on potato crops in Colombia and Ecuador. Hence, the development of resistant cultivars is an alternative for their control. However, breeding initiatives for durable resistance using molecular tools are limited due to the genome complexity and high heterozygosity in autotetraploid potatoes. To contribute to a better understanding of the genetic basis underlying the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 96 publications
(110 reference statements)
0
8
0
3
Order By: Relevance
“…In earlier sections of this review, some polyploids were shown to be more tolerant to abiotic stress induced by genome expression regulation leading to changes in physiological traits, hormonal production, or better antioxidant systems. QTL analysis revealed quantitative resistance for Phytophthora infestans and Tecia solanivora in 4x potato ( Santa et al, 2018 ). Tetraploid and 3x banana cultivars had little damage due to nematodes and did not significantly reduce their plant height ( Dochez et al, 2009 ).…”
Section: Polyploidy Improves Stress Tolerancementioning
confidence: 99%
“…In earlier sections of this review, some polyploids were shown to be more tolerant to abiotic stress induced by genome expression regulation leading to changes in physiological traits, hormonal production, or better antioxidant systems. QTL analysis revealed quantitative resistance for Phytophthora infestans and Tecia solanivora in 4x potato ( Santa et al, 2018 ). Tetraploid and 3x banana cultivars had little damage due to nematodes and did not significantly reduce their plant height ( Dochez et al, 2009 ).…”
Section: Polyploidy Improves Stress Tolerancementioning
confidence: 99%
“…However, with the recent progress in genotyping platforms [28,29] as well as the sequenced potato genome [30], high-density genotyping of tetraploid potato has become possible. Currently, this approach has been used to identify novel QTL and markers associated with different agronomic traits such as late blight resistance [31][32][33], virus resistance [34], tuber quality [35] and other agronomic traits [36]. Santa et al [33] in their study identified six QTL linked to Phytophthora infestans and 15 QTL were mapped for Tecia solanivora in tetraploid potato.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, this approach has been used to identify novel QTL and markers associated with different agronomic traits such as late blight resistance [31][32][33], virus resistance [34], tuber quality [35] and other agronomic traits [36]. Santa et al [33] in their study identified six QTL linked to Phytophthora infestans and 15 QTL were mapped for Tecia solanivora in tetraploid potato. Da Silva et al [34] revealed several major-effect QTL related to Potato virus Y on chromosomes 4 and 5.…”
Section: Introductionmentioning
confidence: 99%
“…Масштабная попытка картирования локусов количествен ных признаков у картофеля была предпринята в 2018 г. (Santa et al, 2018). Исследователи снова выбрали в каче стве объекта тетраплоидный геном картофеля, отмечая его высокую важность для селекции и при этом существенные затруднения в силу высокой гетерозиготности у автотет раплоидного картофеля.…”
Section: локусы количественных признаков у S Tuberosumunclassified